Sierpinski carpet fractal antenna with u-shape defected ground structure (DGS) / Nur Farahain Mohammed - Mohammed, Nur Farahain (2014)
This work highlights the design and fabrication of Sierpinski Carpet Fractal Antenna with Defected Ground Structure (DGS) at center frequency of 5.8 GHz. The antenna was designed and simulated using the Computer Simulation Technology (CST) software. Rogers RT/Duroid 5880 with thickness of 0.38 mm and dielectric constant of 2.2 is used as a substrate of this antenna while the feeding method was inset feed. After the fabricating process, the parameter of the antenna was measured using a Vector Network Analyzer (VNA). This work consists of two measurement results, which are without and with stub matching. An analysis was conducted to compare the performance of the fractal antenna between the different number of iteration and implementation with DGS and without DGS. The third iteration of Sierpinski Carpet Fractal Antenna resulting to a better gain and produce a small size of antenna. The result shows a good agreement between simulation and measurement and satisfied the specification as well.